Coronary occlusive disease and late graft failure after cardiac transplantation. Issue 9 (September 1992) - Mullins, P A; Cary, N R; Sharples, L; Scott, J; Aravot, D; Large, S R; Wallwork, J; Schofield, P M
Abstract : Objective —Coronary occlusive disease is the main cause of late mortality after cardiac transplantation. It has both similarities and differences compared with conventional atherosclerotic coronary disease. The pathophysiology of late graft failure from coronary occlusive disease is unclear at present. We reviewed the experience of this disorder in our cardiac transplant programme. Design —A retrospective analysis of angiographic and pathological data. Setting —A regional cardiothoracic centre and transplant unit. Patients —Of a population of 383 orthotopic cardiac transplant recipients operated upon between January 1979 and June 1990, 447 coronary angiograms were available for review in 193 patients. Thirteen of a possible 18 results of post mortem examinations from patients dying from coronary occlusive disease were available. Main outcome measure —Coronary occlusive disease was defined as any evidence of disease on coronary angiography. Post mortem examinations were performed with standard techniques. Results The angiographic prevalence of coronary occlusive disease was 3% (1/32 patients) and 40% (19/47 patients) at one and five years respectively. Twenty six grafts failed due to coronary occlusive disease compared with 132 graft failures from all causes during this period. Acute thrombosis was present in a large vessel in seven of 13 fatal cases undergoing necropsy (54%). Noticeable large vessel involvement with disease in smaller distal vessels was present in four patients (31%). The remaining two patients (15%) had small vessel disease alone. Twelve of the 13 patients had significant cardiomegaly (cardiac weight ≥400 g) with a mean weight of 510 (range 370-740) g. Conclusion —Coronary occlusive disease is the main late complication after cardiac transplantation. A combination of coronary thrombosis, ischaemia from stenoses of large and small coronary vessels, and cardiomegaly contribute to the graft failure of these patients.